2018
DOI: 10.1016/j.scitotenv.2017.09.038
|View full text |Cite
|
Sign up to set email alerts
|

Association of prenatal exposure to PCDD/Fs and PCBs with maternal and infant thyroid hormones: The Hokkaido Study on Environment and Children's Health

Abstract: Polychlorinated dibenzo-p-dioxins (PCDDs), dibenzofurans (PCDFs) and biphenyls (PCBs) are persistent organic pollutants that are universally detected. Some congeners of PCDDs, PCDFs or PCBs have dioxin-like toxicity, whereas non-dioxin-like PCBs are considered to have different toxicity. Reports of the relationships between prenatal exposure to PCDDs, PCDFs or PCBs and thyroid homeostasis in pregnant women and infants have been inconsistent. The aim of this study was to investigate the effect of maternal serum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 47 publications
0
23
1
Order By: Relevance
“…Similar results have been reported in countries around the world. Analysis of PCB levels in blood from pregnant women in two different Japanese cohorts reported the sum total PCBs (13 examined) of 17.8–362 ng/g lipid [ 52 ], and 20–210 ng/g lipid (29 congeners examined [ 53 ]. Median levels of PCB 153, widely used as an indicator PCB, in the serum of pregnant mothers in Greenland were 107 ng/g lipid [ 42 ], while, in the Ukraine, they were 27 ng/g lipid; the latter was associated with cognitive defects in the children [ 54 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similar results have been reported in countries around the world. Analysis of PCB levels in blood from pregnant women in two different Japanese cohorts reported the sum total PCBs (13 examined) of 17.8–362 ng/g lipid [ 52 ], and 20–210 ng/g lipid (29 congeners examined [ 53 ]. Median levels of PCB 153, widely used as an indicator PCB, in the serum of pregnant mothers in Greenland were 107 ng/g lipid [ 42 ], while, in the Ukraine, they were 27 ng/g lipid; the latter was associated with cognitive defects in the children [ 54 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since Japanese people intake more than 80 % of the PCBs via seafood, it is assumed that OH-PCB profiles in our participants are mainly derived from seafood (Mori et al 2014). The concentrations of precursors of 4-OH-CB187, PCB-183 and PCB-187 (measured as PCB-182 and 187), were 1.6 and 5.8 ng/g lipid weight, respectively among participants in this study, which were predominant PCBs with rather high levels compared to other PCBs in our earlier study (Baba et al 2018). Conversely, 4-OH-CB107, which has been reported as one of the main OH-PCB isomers, was detected only in 47.3 % of serum samples.…”
Section: Discussionmentioning
confidence: 44%
“…Our previous study reported the absence of an association between maternal PCB levels and maternal and neonatal THs (Baba et al 2018). However, current study suggested that OH-PCBs may have effects on fetal thyroid functions than PCBs.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…PCBs have been reported to be positively associated with alteration of maternal thyroid hormones [58]. Other effects on the reproductive systems depend upon the individual PCBs and their concentrations within the mixture [59].…”
Section: Toxicity and Effects On Human Healthmentioning
confidence: 99%